Green Waqf: Konsep, Implementasi, dan Kontribusi terhadap Keberlanjutan Ekologis dalam Perspektif Islam - Qolifatul Amanah; Alfina Khasanatul Khasanah; Mochamad Jibran Nadzaludin Chaq; Rohmad Abubakar Tajudin; Amalia Nuril Hidayati (Ekodestinasi, 2025)
Green waqf is an innovation in Islamic philanthropy integrating traditional waqf principles with environmental preservation, aiming at ecological and social sustainability. This study employs qualitative literature review and descriptive analysis to examine the concept, implementation, challenges, and impacts of green waqf in Indonesia. Findings indicate that green waqf benefits society socially and economically through programs such as waqf forests, renewable energy waqf, sustainable agriculture, and clean water waqf, empowering communities while enhancing environmental quality. Challenges include low waqf literacy, limited technical skills of managers, and absence of specific regulations. Green waqf contributes to sustainable development by asset optimization, creation of green jobs, climate change mitigation, and supporting Sustainable Development Goals (SDGs). Strengthening management and cross-sector collaboration are essential to maximize green waqf’s potential.